Reinforced and prestressed concrete hollow beams under torsion - Luis F. A. Bernardo (Journal of Civil Engineering and Management, 2014)
Recently a new rational theoretical model for beams under torsion has been proposed. This model, called Softened Membrane Model for Torsion (SMMT), is able to predict well the global behaviour of reinforced and prestressed concrete solid beams under torsion. This paper presents a study in order to check the SMMT for reinforced and prestressed concrete hollow beams under torsion. Theoretical predictions from SMMT are compared to some experimental results of hollow beams available in the literature and also with the predictions of another theoretical model previously proposed from the authors. It is shown that SMMT, with some corrections, is able to predict satisfactorily the overall behaviour of reinforced and prestressed concrete hollow beams under torsion.